Pemberdayaan Kelompok Tani Hortikultura di Lahan Pasir melalui Pemanfaatan Kayambang (Salvinia molesta) sebagai Trichokompos: The Empowerment of Horticultural Farming Communities on Sandy Lands to Make Use of Kayambang (Salvinia molesta) to become Trichocompost - Mulyani, Rahmawati Budi; Supriati, Lilies; Melhanah, Melhanah; Kresnatita, Susi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Lebak swamp weeds such as Kayambang (Salvinia molesta) grow abundantly. They can be used as compost, which effectively improves soil fertility, increasing nutrients N, P, and P K quickly and environmentally friendly. The effectiveness of compost fertilizer needs to be increased by adding indigenous microbes as decomposers and biological agents to control plant diseases. The activities carried out to empower horticultural farmer groups on sandy land in Tanjung Pinang Village, Palangka Raya are through socialization, training in composting with three types of antagonist fungus Trichoderma sp. (Trichocompost), facilitate the procurement of weed chopping machines, assist farmers in horticultural crop cultivation, and increase farmers' independence in self-supporting organic fertilizers. The use of Kayambang as Trichocompost with microbial decomposers and indigenous biological agents is new knowledge for partner farmers. The application of Trichocompost on the demonstration plots shows that eggplant plant growth and yields are excellent, meaning that Trichocompost can improve the fertility of sandy soils. Farmers participating in the training stated that the use of Trichocompost could reduce farming costs because it can substitute for manure that has been used by farmers and can meet the self-help needs of organic fertilizers. Participants wanted an advanced mentoring program because the farmers had not yet mastered the isolation or propagation of biological agents and decomposer microbes.